2020
DOI: 10.5853/jos.2019.02236
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation after Intracerebral Hemorrhage and Potential Therapeutic Targets

Abstract: Spontaneous intracerebral hemorrhage (ICH) is a catastrophic illness causing significant morbidity and mortality. Despite advances in surgical technique addressing primary brain injury caused by ICH, little progress has been made treating the subsequent inflammatory cascade. Pre-clinical studies have made advancements identifying components of neuroinflammation, including microglia, astrocytes, and T lymphocytes. After cerebral insult, inflammation is initially driven by the M1 microglia, secreting cytokines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
216
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(242 citation statements)
references
References 157 publications
2
216
0
2
Order By: Relevance
“…First, although TGR5 plays a role in neuroprotection through different mechanisms, such as resistance to apoptosis, oxidative stress resistance, and the maintenance of bloodbrain barrier integrity, in this study, the role of TGR5 in only neuroin ammation was studied. Second, our study showed that TGR5 is also minimally expressed on astrocytes, and the current study con rms that astrocytes are also strongly associated with neuroin ammation [45], and we intend to further evaluate the effect of INT-777 treatment on astrocytes in neuroin ammation in a follow-up study. Third, INT-777 was administered at 1 hour after CLP, and whether the administration of INT-777 within a time frame of 3 hours, 6 hours or longer after CLP would still have a signi cant neuroprotective effect was not evaluated, although this information would be more valuable for clinical application.…”
Section: Discussionsupporting
confidence: 53%
“…First, although TGR5 plays a role in neuroprotection through different mechanisms, such as resistance to apoptosis, oxidative stress resistance, and the maintenance of bloodbrain barrier integrity, in this study, the role of TGR5 in only neuroin ammation was studied. Second, our study showed that TGR5 is also minimally expressed on astrocytes, and the current study con rms that astrocytes are also strongly associated with neuroin ammation [45], and we intend to further evaluate the effect of INT-777 treatment on astrocytes in neuroin ammation in a follow-up study. Third, INT-777 was administered at 1 hour after CLP, and whether the administration of INT-777 within a time frame of 3 hours, 6 hours or longer after CLP would still have a signi cant neuroprotective effect was not evaluated, although this information would be more valuable for clinical application.…”
Section: Discussionsupporting
confidence: 53%
“…After the onset of ICH, a series of neurodegenerative and inflammatory cascade reactions are turned on. These include disruption of the blood–brain barrier, upregulation of chemokines, activation of microglia, mobilization of peripheral lymphocytes to the lesioned brain, apoptosis, and cell death [ 1 ]. As inflammation is closely associated with degeneration in the brain, anti-inflammatory agents may reduce brain damage and improve outcomes in ICH patients.…”
Section: Introductionmentioning
confidence: 99%
“…Microglia and monocytes/macrophages are vital to maintaining homeostasis, acting as phagocytes to scavenge for debris in the CNS after ICH. Targeting these cells may be an ideal therapeutic strategy for stroke [9]. Besides, immuno uorescence staining showed that RXR-α was expressed in microglia/macrophages, astrocytes, and neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanisms are involved in the regulation of tissue healing, hematoma removal, and in ammation resolution. One of the essential mechanisms, especially concerning the neuroin ammation that is incurred by post-hemorrhagic secondary brain injuries, is related to the conversion of the classical activation phenotype (M1) to the alternative activation phenotype (M2) [9]. In the CNS, M2-like microglia/macrophages are e cient phagocytes [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation